O STANIE I POTRZEBACH GUBERNI LITEWSKICH W ROKU 1810 W ŚWIETLE PROTOKOŁÓW CZYNNOŚCI DELEGACJI SZLACHECKIEJ W PETERSBURGU - Godek, Sławomir (Zeszyty Prawnicze, 2016)
ON THE CONDITION AND NEEDS OF THE LITHUANIAN GOVERNORATE IN 1810 IN THE LIGHT OF THE PROTOCOLS FOR THE ACTIVITIES OF THE NOBLE DELEGATION IN ST. PETERSBURG Summary In 1810 a serious rift occurred in Franco-Russian relations. The outbreak of war between the two powers was becoming more and more likely. The Government in St. Petersburg decided to take action to build a pro-Russian faction in Lithuania to weaken the pro-Napoleonic atmosphere there. St. Petersburg’s main collaborator in this work was Michał Kleofas Ogiński, who concocted plans for the restoration, with Russian assistance, of the Grand Duchy of Lithuania and Kingdom of Poland under Russian rule, as a competitor to the Napoleonic Duchy of Warsaw created in 1807. Tsar Alexander I also tried to convince the Lithuanian nobility to accept his policy by granting them the economic incentives and concessions which they sought. In 1810 a delegation of Vilnius nobility went to St. Petersburg and tried to get tax relief, a change in the regulations concerning recruits, the establishment of courts for the demarcation of goods, a change in the organisation and financing of the Vilnius High Court, and an amendment in the procedure for the selection of provincial officials. Similar demands were later presented by the Grodno nobility. The result of these efforts was a series of legal acts issued as of October 1810 which included most of the nobility’s demands.